CRIMINOLOGICAL REVIEW OF THE CRIME OF PROSTITUTION IN A GROUP OF SEXUAL FANTASY PERFORMER ON SOCIAL MEDIA - Tejo, Eko Susanto; Kurniati, Yeti; RAS, Hernawati (Fakultas Hukum Universitas Padjadjaran, 2024)
The development of information technology has changed people's lives with new habits. Almost everyone has a smartphone and has a social media account. Such rapid evolution has changed human life in various fields and has given birth to new forms of legal action. Among them, there are groups of sexual fantasists who use social media as a means to network and find partners. Sexual fantasies are normal and can have a positive impact if applied correctly. However, currently many people use social media to find partners for sexual fantasies by uploading vulgar photos or videos and requiring them to give money, gifts and provide facilities if they want to carry out sexual fantasies with them. This research uses empirical juridical methods and analytical descriptive research specifications. Based on the research results, it can be concluded that the cause of criminal acts of pornography and prostitution in the form of sexual fantasies using social media is the negative impact of the development of information technology, social media, a manifestation of cultural deviation, deviation from norms, and a manifestation of the absence of norms (anomie). Efforts that can be made to overcome this problem are by carrying out cyber patrols, cutting off access to electronic systems that violate laws and regulations, and carrying out repressive efforts against the perpetrators.